A moving target: challenges in treating BRAF-mutant colorectal cancer. (June 2013) - Scott, Aaron J; Leong, Stephen; Messersmith, Wells A; Lieu, Christopher H
SUMMARY  Biomarker-oriented clinical studies have shown mounting evidence for improved efficacy with targeted therapy. Unfortunately, single-agent BRAF inhibition has shown limited efficacy in patients with metastatic BRAF-mutant colorectal cancer. Multiple mechanisms for potential BRAF inhibitor resistance demonstrate the complex biology behind tumorigenesis in colorectal cancer and highlight the obstacles of acquired and intrinsic drug resistance in treating this disease. Biomarker-related strategies with potential predictive value for specific molecular anomalies offer the possibility for improved targeted agents and rational combinations. Synthetic lethality gene array has become a major focus in current research for developing such agents. Combination therapy based on molecular profiles may further enhance individualized patient care.